Switching dynamics in terms of effective time constant to determine switching points using a Debye relaxation equation - Khidhir, Ali H. (Iraqi Journal of Science, 2019)
In this work, the switching dynamics of a Fabry-Perot etalon were analyzed in term of effective time constant, which changes dramatically near the switching points. The switch-ON and switch-OFF have been analyzed numerically using a modified Debye dynamic equation. The method used to determine the solution of the Debye relaxation equations solved numerically to predict the behavior of the etalon for modulated input power.